Fermentation of sugar kelp (Saccharina latissima): exploring the potential of the kelp’s native microbiota as starter culture and the microbiological food safety of fermented products - Pierrick Stévant; Evangelia Zioga; Evangelia Zioga; Jonas Steenholdt Sørensen; Claus Heiner Bang-Berthelsen; Thomas Hagby Dahl; Trygg Barnung; Malin Kleppe; Trond Løvdal (Frontiers in Food Science and Technology)
This study investigated the use of native microbiota from the sugar kelp Saccharina latissima in the form of fermented kelp fluid (FKF) from a spontaneous anaerobic fermentation process as a starter culture (SC) for the fermentation of freshly harvested biomass of the same species. Rapid (<48 h) acidification (pH < 4.3) was achieved for S. latissima inoculated with FKF, at a fermentation temperature of 21°C. Kelp inoculated with a commercial strain of Lactiplantibacillus plantarum (Lp, positive control) reached a similar pH level after 5 days, while kelp with no SC (negative control) did not reach a pH level below 4.3 within 9 days. The microbiota of the FKF-SC as well as the FKF-inoculated S. latissima samples was dominated by lactic acid bacteria (LAB) identified as L. plantarum. The SC in these samples successfully converted mannitol into lactic acid as the main fermentation product. In contrast, a higher production of acetic acid and ethanol was measured in the negative control samples than in other groups; this reflects a different microbial profile, including marine bacteria which could not be identified by MALDI-TOF biotyping. Challenge trials of S. latissima samples from experimental and commercial fermentation processes with Bacillus cereus did not result in the growth of this food pathogen, even at pH levels within a viable range for this species (pH > 4.3). These preliminary results provide a foundation for further isolation of suitable SCs for kelp fermentation in commercial production and for assessing the food safety of fermented kelp. Efficient and safe fermentation processes will increase sustainability in kelp production and enable a broader use of kelp ingredients in food applications.